Análise da formação profissional no Programa Esporte e Lazer da Cidade (PELC): o olhar dos agentes sociais - Andréa Nascimento Ewerton (2010)
Studies of vocational training in sport and recreation are gaining ground in academia, as well as in the public policy field and have become the preferred axis of intention and analysis. The training of professionals in public policy may contribute in the relationship between politics and society, aiming to contribute to a critical reflection of the population with regard to public services. The object of this study is the professional education policy of social agents of the “Programa Esporte e Lazer da Cidade” (PELC), formulated by the Ministry of Sports and implemented through partnerships with public and private agencies, with nonprofit means. For the elaboration of the problem, the following questions were constructed: How is the proposal for professional education in “Programa Esporte e Lazer da Cidade” (PELC) developed? What is the view of the PELC social agents on the proposed training? The objectives of this study were to analyze the proposed formation of PELC, under the view of social agents, from the understanding of the following aspects: the content of the education program, the relationship between the training modules and the development of the activities, the relationship between theory and practice in actions of sports and leisure and the vision of Public Policy. The survey was developed from the bibliographic research, in the perspective of deepening the understanding of the concepts of the creation of the program, which, added to the field survey, allowed the understanding of the coherence between the education project proposed by the program and the practical training which was implemented. For data collection, the technique used was the semi-structured interview, implemented with agents and managers of three (3) entities that implement the program, followed by the application of the technique of content analysis to process the information collected. Training is considered by officials as a key element to the qualification of actions developed in the agreements; moreover it was possible to realize the difficulties in monitoring and tracking the actions of training in particular the module in service training. This limit is directly involved in the process of learning the developed content. Another important point to be highlighted is the diverse profile of staff, which indicates difficulties in the selection of content and methodological definition in actions of training.